Non-destructive characterization of lithium deposition at the Li/separator and Li/carbon matrix interregion by synchrotron X-ray tomography. (August 2019) - Dong, Kang; Osenberg, Markus; Sun, Fu; Markötter, Henning; Jafta, Charl J.; Hilger, André; Arlt, Tobias; Banhart, John; Manke, Ingo
Abstract: Inherently uncontrollable Li electrodeposition has significantly hindered the practical application of Li metal batteries largely due to a dendritic deposition which can initiate an internal short circuit and gives rise to severe safety issues. The understanding of the fundamental electrodeposition mechanism is, however, elusive and limited due to a lack of feasible in situ characterization techniques. Here synchrotron X-ray tomography was employed to noninvasively visualize Li deposition at the lithium/separator and lithium/carbon matrix interregion. A higher concentration of widely distributed deposition sites was observed under an increased current density. The 3D morphology and distribution of deposited Li within the widely used Celgard ® 2325 polyolefin separator are, for the first time, visualized in situ, thus promoting the understanding of the short-circuiting process of Li metal batteries. In addition, we also visualized and quantified the spatial distribution of Li depositions inside a porous carbon host to unravel the deposition behavior that can hardly be probed by surface imaging techniques. The Li electrodeposition behavior found here could help to promote the understanding and development of surface modifications related to Li anodes, separators as well as novel 3D geometry electrode designs for accommodation of Li depositions and alleviation of volumetric changes. Graphical abstract: Image 1 Highlights: The 3D morphology and distribution of Li deposition within Celgard ® 2325 separator are visualized in situ. An increased current density was found to bring about a higher concentration Li deposition sites. The spatial distribution of Li depositions inside a porous carbon host is visualized and quantified.